Effectiveness of Medical Treatment of Cushing’s Disease: A Systematic Review and Meta-Analysis - Simões Corrêa Galendi, Julia; Correa Neto, Afonso Nogueira Simões; Demetres, Michelle; Boguszewski, Cesar Luiz; Nogueira, Vania dos Santos Nunes (Frontiers in Endocrinology, 2021)
Objective: The objective of this systematic review was to evaluate effectiveness and safety of pasireotide, cabergoline, ketoconazole, levoketoconazole, metyrapone, osilodrostat and temozolomide for the treatment of Cushing’s disease (CD). Methods: Primary outcomes were proportion of CD control, adverse events (AE) and reduction of urinary free cortisol. Search strategies were applied to Embase, Medline, and CENTRAL. Independent reviewers assessed study eligibility, extracted data, and evaluated risk of bias. Standardized mean difference was calculated with 95% confidence interval (CI) for continuous data (i.e. pre- and post-intervention). Random meta-analyses for proportion of CD control and AE were conducted. Results: Twenty-nine controlled and non-controlled studies were included. No study with temozolomide and levoketoconazole and one study with osilodrostat fulfilled inclusion criteria. Meta-analyses of proportion of CD control was 35% for cabergoline (95% CI 27-43%, 6 studies, 141 participants), 44% for pasireotide (95% CI 25-35%, 8 studies, 522 participants), 41% for ketoconazole (95% CI 36-46%, 6 studies, 450 participants), 66% for metyrapone (95% CI 46-87%, 4 studies, 66 participants) and of 66.4% for osilodrostat (95% CI: 57.9, 74.3, 97 participants, 1 study). One study compared two different treatments (cabergoline vs ketoconazole), and no statistical difference was observed in CD control (RR: 0.53, 95% CI: 0.15 to 1.87, 14 participants, very low certainty of evidence). The most frequent AE associated with pasireotide was hyperglycemia; dizziness and nausea with cabergoline and metyrapone, and elevated transaminases with ketoconazole. Conclusion: The superiority of one drug over another could not be determined due to lack of controlled studies, but the proportion of disease control identified in our meta-analysis may support clinical decision. New therapeutic options should be investigated, due to the limited efficacy and tolerability of the currently available medical treatment for patients with Cushing’s disease.